Metabolomics of Dynamic Changes in Insulin Resistance Before and After Exercise in PCOS - Halama, Anna; Aye, Myint Myint; Dargham, Soha R.; Kulinski, Michal; Suhre, Karsten; Atkin, Stephen L. (Frontiers in Endocrinology, 2019)
Background: Plasma elevated levels of branched chain amino acids (BCAA) and aromatic amino acids (AAA) have been associated with obesity and insulin resistance, but their relationship to stimulated insulin resistance (IR) in PCOS and in response to exercise is unknown. Indeed, it is unknown whether the mechanism of IR in PCOS is mediated through changes in the metabolome. Methods: Twelve women with polycystic ovary syndrome (PCOS) and ten age and body mass index matched controls completed an eight week supervised exercise program at 60% maximal oxygen consumption. Before and after the exercise program, all participants underwent maximal IR stimulation with intralipid infusions followed by insulin sensitivity (IS) measurement by hyperinsulinaemic euglycaemic clamps. Amino acid profiles and metabolites were taken at baseline and at maximal insulin resistance stimulation before and after the exercise program. Results: At baseline, PCOS subjects showed increased leucine/isoleucine, glutamate, methionine, ornithine, phenylalanine, tyrosine and proline (p<0.05) that, following exercise, did not differ from controls. While compering within the groups, no significant changes in the amino acid levels before and after exercise were observed. Exercise improved VO2 max (p<0.01) but did not alter weight. Amino acid profiles were unaffected by an acute increase in IR induced by the lipid infusion. IS was lower in PCOS (p<0.001) and was further decreased by the lipid infusion in both PCOS and controls. Although, exercise improved IS in both PCOS and in controls, the IS remained compromised in PCOS. Conclusion: The baseline amino acid profile in PCOS reflected that seen in obese subjects and differed to controls. After exercise, and despite no change in weight in either group, there were no differences in the amino acid profile between PCOS and controls. This shows that exercise may normalize the amino acid metabolome, irrespective of weight.